1988
DOI: 10.1111/j.1600-0722.1988.tb01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sodium fluoride solution and a varnish with different fluoride concentrations on enamel remineralization in vitro

Abstract: – To study the efficacy of sodium fluoride varnishes and a NaF solution in remineralization of enamel, 120 slabs of non‐carious human enamel enamel were presoftened for 6 h and randomly divided into six groups. The slabs were stored in synthetic saliva for 9 days, except for a daily 30‐min immersion in 0.1 M lactic acid‐NaOH buffer. During the 9‐day period, one group of the slabs received no treatment, and the rest were treated once or three times with 2.3% or 1.1% sodium fluoride varnish Duraphat, or nine ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…However, the efficacy of fluoride varnishes and gels in decreasing demineralization and enhancing remineralization of dental hard tissues is similar. 22,23 On the other hand, the protective effects of laser irradiation of enamel and dentine from demineralization have gained increasing attention in recent years. Several types of lasers, such as ruby, CO 2 , Nd:YAG, and argon, with different operational modes and energy outputs have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of fluoride varnishes and gels in decreasing demineralization and enhancing remineralization of dental hard tissues is similar. 22,23 On the other hand, the protective effects of laser irradiation of enamel and dentine from demineralization have gained increasing attention in recent years. Several types of lasers, such as ruby, CO 2 , Nd:YAG, and argon, with different operational modes and energy outputs have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising, since a si lane fluoride varnish (Fluor Protector®) with approxi mately the same fluoride concentration (0.7%) has been found effective in caries prevention in some clin ical studies [Salem et al, 1979;Clark et al, 1985], and even much lower concentrations have inhibited en amel dissolution in vitro and in vivo [De Bruyn et al, 1986, 1988. The difference may be explained by dif ferent physicochemical properties of the two types of varnishes [De Bruyn and Arends, 1987, a review].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the effect of a fluoride regimen in caries prevention or de-and remineralisation of en amel has not been directly proportional to the fluo ride content of the preparation [ten Cate and Simons, 1986, De Bruyn et al, 1986, 1988Goorhuis and Purdell-Lewis, 1986;Ripa et al, 1988]. Based on this, the fluoride concentrations of some professionally ap plied topical fluorides seem unnecessarily high.…”
mentioning
confidence: 99%
“…The result is loss of at least part of the loosely bound fluoride important for remineralization. In this study we decided to enhance the remineralization potential of the varnishes by not rinsing, like other authors [Seppä, 1988;Scholtanus et al, 1986]. If FV enhances the formation of a layer of soluble fluoride, mainly CaF 2 -like deposits on enamel [Nelson et al, 1983], this slowly dissolving material is an important source of fluoride for enhancement of remineralization and uptake in the outer enamel over a long time period.…”
Section: Discussionmentioning
confidence: 99%
“…Attin et al [1997] used a Duraphat varnish to successfully enhance remineralization of bleached enamel specimens. Seppä [1988] suggested that the benefits of FV are related more to their ability to enhance remineralization of primary caries than to increase the fluoride content of the surface. Her results suggest that the efficacy of the varnishes was not proportional to their fluoride concentration but rather to the number of applications.…”
Section: Discussionmentioning
confidence: 99%